Mechanism Prediction of Monotropein for the Treatment of Colorectal Cancer by Network Pharmacology Analysis - Li Chong; Hou Shao-Zhen; Zhou Hua (KeAi Communications Co., Ltd., 2020)
Objective: To discover the pharmacological mechanisms of monotropein in colorectal cancer by network pharmacology methods. Methods: The main-candidate-target network was constructed by the prediction of targets of monotropein, collection of therapeutic targets of colorectal cancer drugs, and construction of the target network and layers of screening. The data were interpreted by pathway enrichment and target score calculation. Results: This study: (1) Demonstrated the potential of monotropein to be a multi-target drug against colorectal cancer using a computational approach; (2) Discovered 10 candidate targets of monotropein, among which protein kinase B (AKT1) exhibited the highest relevance and importance to colorectal cancer and proto-oncogene tyrosine-protein kinase Src (SRC), Bruton's tyrosine kinase (BTK), and heat shock protein HSP 90-alpha (HSP90AA1) also exhibited high relevance; (3) Observed 32 possible pathways related to the effects of monotropein on colorectal cancer, which might explain the mechanism of its action; and (4) Established a method to assess the importance of targets in the network. Conclusions: This study offered clues for the mechanism of the bioactivities of monotropein against colorectal cancer by network analysis. Monotropein has the potential to be a multi-target drug against colorectal cancer, which lays the foundation for its clinical applications and further study. Keywords: colorectal cancer, monotropein, network pharmacology, target, Protein kinase B (AKT1)